Inferring palaeoecology in extinct tremarctine bears (Carnivora, Ursidae) using geometric morphometrics - Figueirido, Borja (2010)
In this study, we explore the ecomorphological patterns of extinct tremarctine bears inSouth America during the Great American Biotic Interchange (GABI). These patternsare used to derive paleoautoecological inferences in extinct tremarctines and theirpaleosinecological relationships within Plio-Pleistocene ecosystems. We used geometricmorphometrics of landmark data to recover the shape of the craniomandibular skeletonof bears. The results reveal different ecomorphological adaptations in extincttremarctines during the Plio-Pleistocene of South America. Indeed, these bears couldhave increased the percentage of plant matter in their diets accordance with theincreased diversity of large carnivores in South America after the GABI. Omnivorousbears retain the ability to behave as carnivores or herbivores depending on resourceavailability. This fact strongly supports that living and extinct bears are one of the mostecologically and morphologically adaptable members of the large carnivore guild.Moreover, their skull morphology could reflect ecological adaptations under differentselection pressures with the required evolutionary time.